- URGENSI PENGEMBANGAN E-MODUL BERDIFERENSIASI BERBASIS LOKALITAS UNTUK MENINGKATKAN LITERASI PESERTA DIDIK SEKOLAH DASAR - Mian Anita; Syarifuddin; Mochamad Amri Santosa (Jurnal Penelitian Pendidikan IPA, 2026)
21st century education demands a more adaptive, creative, and contextual learning approach, especially in improving student literacy. This study aims to examine the urgency of developing locality-based differentiated e-modules as an effort to improve elementary school student literacy. This research employed a quantitative descriptive method focused on exploring needs based on percentage values, supported by the actual learning conditions in elementary schools. Based on an analysis of the needs of students and teachers through questionnaires and interviews, it was found that students and teachers need learning media that are more interesting, relevant to the surrounding environment, and can be adjusted to individual learning styles and abilities. Differentiated e-modules based on local wisdom have the potential to meet these needs by providing a more personal and contextual learning experience. These findings indicate that the development of locality-based differentiated e-modules is very important in order to improve student literacy, enrich learning experiences, and prepare students to face increasingly complex educational challenges. Therefore, the development of technology-based learning media needs more attention in efforts to improve the quality of elementary education in Indonesia. The level of student needs is 76.4 which is included in the need category, and the level of teacher needs is 83.3 which is included in the very need category.